Ecological Study Of Polychaeta (Family capitelidae) As A Bio-Indicator of Organic Pollution in Kasturian And Salero Coastal Waters City Of Ternate - Irham, Irham; Salim, Fajria Dewi; Alhadad, M. Said (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Pollution of the marine environment hurts the survival of aquatic organisms. One of the impacts caused by human activities is sea pollution. One source of marine pollution comes from organic waste, namely waste that comes from household waste that enters the waters. It affects the ecology of organisms and creates species that are susceptible to pollutants. This study aimed to determine the level of organic matter contamination using the species diversity index and the dominance index of Polychaeta (family Capitelidae). This research was carried out around the coastal waters of the North Ternate District from March to July 2020. The parameters observed were determining the substrate's texture, organic matter, diversity and dominance, and environmental parameters, which were then determined by the level of water pollution. The results obtained found as many as 156 individual worms consisting of 2 (two) species, namely Heteromastus sp and Capitella capitata. The composition of the substrate consists of sand, silt and clay. Overall the substrate is dominated by dusty loams and sandy loams. The analysis of the diversity index, dominance index and dissolved oxygen content shows that Kasturian and Salero coastal waters in a heavily polluted condition.